Rural villages as a sustainable approach for the provision of farm workers housing related needs in Mpumalanga Province - Meshack, Mahamba Mlayedwa (My University, 2011)
The idea of a rural village is a new settlement concept that has been piloted by the Steve Tshwete Municipality in Mpumalanga Province. It has been used as a mechanism for providing basic services and security of tenure to farm dwellers. The purpose of this research is to assess if rural villages can be a sustainable approach for the provision of farm workers housing related needs. Doornkop Rural Village was used as a case study. The location of the rural villages far from urban centres where economic opportunities exist, creates problems such as high transport costs and decreases chances of getting alternative employments. Rural villages are costly to service as they are located far from the municipal bulk infrastructure. This may lead to creation of dormitory settlements. On the contrary, location rural villages 15km closer to urban areas may encourage urban sprawl and sterilisation of agricultural potential of adjacent farms. The rate of revenue collection at rural villages is very low as most of the households are indigent. Therefore, rural villages are not a sustainable approach for the provision of farm workers housing related needs